Unraveling the pectinolytic function of Bacteroides xylanisolvens using a RNA-seq approach and mutagenesis. (December 2016) - Despres, Jordane; Forano, Evelyne; Lepercq, Pascale; Comtet-Marre, Sophie; Jubelin, Grégory; Yeoman, Carl; Miller, Margret; Fields, Christopher; Terrapon, Nicolas; Bourvellec, Carine; Renard, Catherine; Henrissat, Bernard; et al.
Abstract Background Diet and particularly dietary fibres have an impact on the gut microbiome and play an important role in human health and disease. Pectin is a highly consumed dietary fibre found in fruits and vegetables and is also a widely used additive in the food industry. Yet there is no information on the effect of pectin on the human gut microbiome. Likewise, little is known on gut pectinolytic bacteria and their enzyme systems. This study was undertaken to investigate the mechanisms of pectin degradation by the prominent human gut symbiontBacteroides xylanisolvens . Results Transcriptomic analyses ofB. xylanisolvens XB1A grown on citrus and apple pectins at mid- and late-log phases highlighted six polysaccharide utilization loci (PUL) that were overexpressed on pectin relative to glucose. The PUL numbers used in this report are those given by Terrapon et al. (Bioinformatics 31(5):647-55, 2015) and found in the PUL database:http://www.cazy.org/PULDB/ . Based on their CAZyme composition, we propose that PUL 49 and 50, the most overexpressed PULs on both pectins and at both growth phases, are involved in homogalacturonan (HG) and type I rhamnogalacturonan (RGI) degradation, respectively. PUL 13 and PUL 2 could be involved in the degradation of arabinose-containing side chains and of type II rhamnogalacturonan (RGII), respectively. Considering that HG is the most abundant moiety (>70 %) within pectin, the importance of PUL 49 was further investigated by insertion mutagenesis into thesusC-like gene. The insertion blocked transcription of thesusC-like and the two downstream genes (susD-like/FnIII ). The mutant showed strong growth reduction, thus confirming that PUL 49 plays a major role in pectin degradation. Conclusion This study shows the existence of six PULs devoted to pectin degradation byB. xylanisolvens, one of them being particularly important in this function. Hence, this species deploys a very complex enzymatic machinery that probably reflects the structural complexity of pectin. Our findings also highlight the metabolic plasticity ofB. xylanisolvens towards dietary fibres that contributes to its competitive fitness within the human gut ecosystem. Wider functional and ecological studies are needed to understand how dietary fibers and especially plant cell wall polysaccharides drive the composition and metabolism of the fibrolytic and non-fibrolytic community within the gut microbial ecosystem.